Restoring Soil Health: A Study on Effective Microorganisms and Maize Straw Applications - Shichao Chen; Qing Zhang; Tongtong Liu; Min Yan; Luying Shao; Zhi Jia (Agronomy, 2025)
Soil degradation caused by mining activities has seriously affected the ecological environment of mining areas. Improving the soil quality is the key to solving this problem. This study examined the impact of adding Effective Microorganism (EM) agents and maize straw to the soil from the dump of the Ordos Rongheng open-pit coal mine. We conducted a two-factor complete experiment, varying the amounts of EM agents (0 g·kg−1, 0.1 g·kg−1, 0.2 g·kg−1, 0.3 g·kg−1, and 0.4 g·kg−1) and maize straw (0 g·kg−1, 5 g·kg−1, 10 g·kg−1, 15 g·kg−1, and 20 g·kg−1). Changes in the soil’s physical, chemical, and biological properties were assessed using a six-month-long potting experiment, and a minimum data set was established for soil quality evaluation. Our results indicated that both EM agents and maize straw improved the soil quality. Both additions reduced the soil’s bulk density and pH while increasing its porosity, organic matter, total available nutrients, enzyme activity, and microbial diversity. However, maize straw had no significant effect on the soil moisture content and total available phosphorus, and EM agents did not significantly impact organic matter. The interaction between the two treatments was not significant for soil moisture content, capillary porosity, and total potassium. Finally, we identified five key indicators affecting soil’s quality: the bulk density, available potassium, alkaline phosphatase, bacterial Chao1 index, and fungal Shannon index. The soil quality index (SQI) ranged from 0.158 to 0.568, with the highest SQI being observed with 0.1 g·kg−1 EM agents and 20 g·kg−1 maize straw, which was significantly higher than those from other treatments. New insights into the improvement of soil quality in open-pit mines are provided by these results, which may help guide future ecological restoration of mines.